2023
DOI: 10.3350/cmh.2022.0364
|View full text |Cite
|
Sign up to set email alerts
|

Eating, diet, and nutrition for the treatment of non-alcoholic fatty liver disease

Abstract: Shire, speaker fees from Bristol-Myers Squibb, Falk, Gilead, Intercept and MSD, as well as travel support from AbbVie, Falk, Gilead, and Intercept. He is also co-inventor of patents on the medical use of 24-norursodeoxycholic acid. List of abbreviations: BMIbody mass index; CAPcontrolled attenuation parameter; DNLde-novo lipogenesis; HCDhigh-carbohydrate diet; IFintermittent fasting; IHLCintrahepatic lipid content; LCDlow-carbohydrate diet; LSMliver stiffness measurement; MD -Mediterranean diet; MUFAmono-unsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 198 publications
(292 reference statements)
0
7
0
1
Order By: Relevance
“…Several detailed reviews provide an extended and in depth background on the evidence for the use of certain diets in NAFLD (15,16,37). Evidence can be briefly summarised as follows:…”
Section: Dietary Interventions In Nafldmentioning
confidence: 99%
“…Several detailed reviews provide an extended and in depth background on the evidence for the use of certain diets in NAFLD (15,16,37). Evidence can be briefly summarised as follows:…”
Section: Dietary Interventions In Nafldmentioning
confidence: 99%
“…4 Numerous epidemiological studies have also indicated a dose-response relationship between sugar-sweetened beverage consumption and both NAFLD prevalence and incidence. 5 Consumption of fructose causes harmful changes to the composition of the gut microbiome. 6 The Framingham Heart Study reconfirmed that frequent consumers of sweetened beverages face a significantly elevated risk of developing NAFLD compared to non-consumers.…”
Section: Correspondencementioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES) data have demonstrated a link between increased added sugar consumption and a higher prevalence of NAFLD and obesity [ 4 ]. Numerous epidemiological studies have also indicated a dose-response relationship between sugar-sweetened beverage consumption and both NAFLD prevalence and incidence [ 5 ]. Consumption of fructose causes harmful changes to the composition of the gut microbiome [ 6 ].…”
mentioning
confidence: 99%
“…Currently, pharmacological treatments for NAFLD lack both safety and efficacy, and lifestyle interventions such as weight loss, a balanced diet, and physical exercise remain among the best treatments for NAFLD [ 2 ]. A growing number of studies have shown a negative correlation between the Mediterranean diet and the incidence of NAFLD [ 3 ]. The Mediterranean diet, characterized by a high content of polyphenols, carotenoids, vitamins, and polyunsaturated fats, has anti-inflammatory and antioxidant effects, and has been shown to be highly effective in reducing the risk of metabolic syndrome [ 4 ].…”
Section: Introductionmentioning
confidence: 99%